Move aside, mr. ford : to make room for the new, more agile micro-factories - Kleinhample, Masa, ....-; Kleinhample, Jon, ....- (Tielt : Lannoo, 2016)
A reasearch project sponsored by Lannoo publishing company in Belgium, Microfactories: Move aside Mr. Ford, is an exploration into a new breed of entrepreneur. This new breed operates what we define as an evolution of the traditional factory, something smaller and more agile, the micro-factory. A micro-factory is an atelier, a container studio, a re-purposed factory hall, where digital technology drives a new understanding of customization and adaptability, all in the hands of creative entrepreneurs. This is not your grandfather's bakery, or your grandmother's steel shop, but a place where creative businesses combine traditional techniques with new technologies, resulting in the emergence of adaptable factories, places where the endless repetition of the assembly line has been eliminated. A new breed of creative entrepreneur operates these micro-factories in a global, interconnected economy driven by digital technology. These businesses operate upon an elevated plateau, where technology and tradition weave together to form a remarkably romantic but inimitably commercial enterprise. This 312 page book is a careful examination introspective glance into our own studio and 23 other micro-factories around the world. Complete editorial idea, photography, writing and graphic design of the book have been done by Klein Agency.
Keywords: Ondernemen